ARTIFICIAL INTELLIGENCE AS A TOOL FOR ENHANCING THE QUALITY OF PROFESSIONAL TRAINING FOR FUTURE SPECIALISTS IN THE FIELD OF ELEMENTARY MATHEMATICS EDUCATION IN THE CONTEXT OF DISTANCE LEARNING - Dolynyuk , Myroslava Myronivna; Shuper , Tetiana Mykolayivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article examines the potential of using Artificial Intelligence as a means to enhance the quality of professional training for future primary education teachers in the field of mathematics. It outlines the directions for its application during the training of junior specialists under distance learning conditions. provides examples of pedagogical tasks for specific topics of the disciplines «Methodology of Teaching Mathematical Education Sector» and «Fundamentals of Elementary Mathematics Course».